Pandangan Dunia Islam dan Transformasi Digital: Antara Peluang dan Tantangan - Hamdani, Arfan; Hermawan, Rudi; Samiran, Muhammad (Lembaga Yasin AlSys, 2025)
The digital transformation era has profoundly reshaped human life, including that of the Muslim community. Within the Islamic worldview (Islam worldview), technology is regarded as a wasilah (means) to fulfill the purpose of human existence as servants and vicegerents of Allah. Therefore, its use must be grounded in the values of tawhid, justice, trustworthiness, and public benefit (maslahah). However, the dominance of secular, materialistic, and liberal values in digital spaces presents serious challenges, such as spiritual disorientation, identity crises, and the marginalization of religious values in digital life. Addressing these challenges requires integrative and sustainable strategies, including the strengthening of Islamic digital literacy, the production of meaningful content, the development of technology aligned with shariah ethics, and collaboration among scholars, educators, technologists, and Muslim communities. This approach aspires to position Muslims not merely as consumers but as key contributors in shaping a healthy, productive, and divinely guided digital ecosystem. Thus, digital transformation becomes a strategic opportunity to reestablish Islam as a rahmatan lil-‘alamin (mercy to all creation) within modern civilization.